2004
DOI: 10.1176/appi.ajp.161.6.1116
|View full text |Cite
|
Sign up to set email alerts
|

3-T Proton MRS Investigation of Glutamate and Glutamine in Adolescents at High Genetic Risk for Schizophrenia

Abstract: The finding of glutamate/glutamine abnormalities in a group of subjects at high genetic risk for schizophrenia lends support for both the glutamate dysfunction and neurodevelopmental hypotheses for schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 13 publications
9
92
0
3
Order By: Relevance
“…A few years later, similar results in first-episode schizophrenic patients were reported in the prefrontal cortex and the hippocampus (48). Furthermore, a study of nonpsychotic adolescents at genetic risk for schizophrenia found significantly increased Glx in the right medial frontal lobe (49). Glutamine levels in the anterior cingulate and thalamus reduce as disease progresses and this reduction correlated with progressive gray Figure 4.…”
Section: Proton Mrs Studies Of Glutamatesupporting
confidence: 53%
“…A few years later, similar results in first-episode schizophrenic patients were reported in the prefrontal cortex and the hippocampus (48). Furthermore, a study of nonpsychotic adolescents at genetic risk for schizophrenia found significantly increased Glx in the right medial frontal lobe (49). Glutamine levels in the anterior cingulate and thalamus reduce as disease progresses and this reduction correlated with progressive gray Figure 4.…”
Section: Proton Mrs Studies Of Glutamatesupporting
confidence: 53%
“…Starting from this prodromal phase, progressive changes in brain volume, including the PFC, and disturbances in Glu-neurotransmission (Marsman et al 2013) may occur. Tibbo et al (2004) found significantly higher levels of Glu in the right medial frontal lobe of HR compared to controls, although other studies failed to replicate these findings. Purdon et al (2008) finding the absence of differences in Glu metabolites levels between HR and HC in the same brain region, as was for Yoo et al (2009).…”
Section: Discussionmentioning
confidence: 87%
“…Although not yet consistently supported by MRS studies, which have shown increased levels of Glu in the mesPFC, 49 and reduced levels in anterior cingulate gyrus 46 and thalamus 50 of schizophrenia subjects compared with controls, based on the hypoglutamatergic hypothesis of schizophrenia, [51][52][53] we predicted a reduction in Glu in patients compared with controls.…”
Section: Introductionmentioning
confidence: 79%